Ultrafiltrated extracts of fermented okara as a possible serum alternative for cell culturing: potential in cultivated meat production - Teng, Ting Shien (2023)
Animal serum such as fetal bovine serum (FBS) is a commonly used irreplaceable essential supplement in cell culture media. However, the use of FBS has associated ethical, biosafety, and cost concerns in industrial cell culture and limits application in cultivated meat production. Okara is an agro-waste generated in huge abundance daily, which can be biotransformed by fermentation. Different fractions of the fermented okara extracts were prepared by ultrafiltration according to their molecular weight and termed as unfractionated, 50 kDa, 10 kDa, and 3 kDa. Our results from the MTT assay showed that the 50 kDa fractionated fermented okara extract at 1 mg/mL was the most effective serum replacement under daily replenishment of media, as the viability of both HEK293 and HepG2 cells achieved a relative growth efficiency (RGE) of 70% compared to that of the positive control where traditional FBS was used (RGE was 100%). To understand the mechanism behind this, the metabolite profiles of 24 and 72 h HEK293 and HepG2 spent cell culture media were taken for analysis using gas chromatography-mass spectrometry. To explore the potential of using fermented okara extracts in cultivated meat production, the extracts were added to C2C12 and immortalized porcine myoblast cultures where growth was observed over 72 and 48 h, respectively. In conclusion, our study demonstrated that ultrafiltrated potential fermented okara extract could be a potential novel serum alternative for cellular agriculture use.